Formulasi Lotion Ekstrak Etanol Daun Kopi Arabika (Coffea arabica L.) dan Ekstrak Etanol Daun Perepat (Sonneratia alba Sm.) Sebagai Antioksidan - Maizatul Ummah (Departement of Pharmacy, Faculty of Mathematics and Natural Science, Udayana University, 2025)
Skin damage can be triggered by exposure to free radicals, making antioxidants important as skin protection agents. Arabica coffee leaves (Coffea arabica L.) and perepat leaves (Sonneratia alba Sm.) are known to have potential as natural sources of antioxidants. This study aims to formulate and evaluate lotion preparations containing ethanol extracts of these two leaves based on their physical characteristics and antioxidant activity. Four lotion formulas were prepared, namely K (without extract addition), FI (0.1% Arabica leaves + 1.0% perepat leaves), FII (0.5% Arabica leaves+ 0.5% perepat leaves), and FIII (1.0% Arabiva leaves + 0.1% Perepat leaves). The evaluation was conducted using an accelerated test (cycle test) on organoleptic properties, homogeneity, stability, pH, spreadability, adhesion, viscosity, emulsion type, and antioxidant activity, which were then analyzed descriptively. The results showed that formulas FII and FIII met the physical stability requirements. The antioxidant activity test showed that formula FIII had the highest activity with an IC₅₀ value of 45.41 ± 0.52 ppm compared to FI and FII. Based on these results, it can be concluded that lotion formula FIII is the best formulation in terms of stability and antioxidant effectiveness.